2018
DOI: 10.3928/01913913-20180621-01
|View full text |Cite
|
Sign up to set email alerts
|

Icare-Pro Rebound Tonometer Versus Hand-held Applanation Tonometer for Pediatric Screening

Abstract: Pediatric IOP measurements determined using the new Icare-Pro rebound tonometer showed good correlation with those obtained using the hand-held Perkins applanation tonometer in a routine clinical examination with no need for general anesthesia. [J Pediatr Ophthalmol Strabismus. 2018;55(6):382-386.].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…When used to take readings in young or uncooperative patients under anaesthesia, the handheld Perkins applanation tonometer is still considered as a reference device. However, the literature confirms reliable and repeatable measurements using rebound devices prior to RT200 in patients with PCG (Martinez‐de‐la‐Casa et al., 2009; Borrego Sanz et al., 2016; Arribas‐Pardo et al., 2018).…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…When used to take readings in young or uncooperative patients under anaesthesia, the handheld Perkins applanation tonometer is still considered as a reference device. However, the literature confirms reliable and repeatable measurements using rebound devices prior to RT200 in patients with PCG (Martinez‐de‐la‐Casa et al., 2009; Borrego Sanz et al., 2016; Arribas‐Pardo et al., 2018).…”
Section: Discussionmentioning
confidence: 85%
“…This was followed by reports of similar results using the iCare Pro (Borrego Sanz et al., 2016), which showed excellent agreement with PAT in patients with PCG examined under anaesthesia (ICC = 0.74), and in 64% the difference was < 3mmHg. Results were also much improved when measurements were compared between Icare Pro and PAT in healthy children (ICC = 0.857, and mean IOP difference between devices 0.26) (Arribas‐Pardo et al., 2018). The previous version to RT200 was iCare ic100, and while no study has examined its efficacy in PCG, in adults with glaucoma it has shown good agreement with Goldmann applanation tonometry (ICC = 0.93) (9).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The deceleration of the probe is calculated into the IOP and displayed on the device after six rebounds per measurement [8, 9]. Due to its comfortableness and ease of use, iCare has gained much attention in clinical practice [10], especially in children [11]. Non-contact tonometer (NCT) is developed over 30 years [12].…”
Section: Introductionmentioning
confidence: 99%
“…2 The introduction of new IOP measuring devices allows for complementary pressure measurements to GAT such that more measurements can be obtained in the ophthalmology office. [3][4][5] Icare200 (IC200, Tiolat Oy, Helsinki, Finland) is the new version of Icare (Fig. 1).…”
mentioning
confidence: 99%